If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying F(x) = 2x + -1x + 1 Multiply F * x xF = 2x + -1x + 1 Reorder the terms: xF = 1 + 2x + -1x Combine like terms: 2x + -1x = 1x xF = 1 + 1x Solving xF = 1 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -1x + xF = 1 + 1x + -1x Combine like terms: 1x + -1x = 0 -1x + xF = 1 + 0 -1x + xF = 1 Reorder the terms: -1 + -1x + xF = 1 + -1 Combine like terms: 1 + -1 = 0 -1 + -1x + xF = 0 The solution to this equation could not be determined.
| f-12=10 | | d+32=70 | | f(x)=-x^2+10x+17 | | f(x)=x^2+10x-17 | | 2(x^2-1)=(x^2-3) | | 6.1c=42.7 | | 4x^2+2=144 | | H(x)=4x-4x+21 | | 3/4=12y | | .999q^2-6q+15=0 | | w+-5=15 | | 83=24.5x+9.5 | | F(x)=-x-4x+1 | | 2m^(5)n^(7)/14m^(6)n^(3) | | 4z-12=-3z+16 | | 7/n-6=5/11 | | t^2=t+8 | | 42=2.1 | | X=20t-4t^2 | | 2/3x-7/9 | | F(x)=-x+2x+5 | | 2x-3(-1+x)=-1 | | 1/5(1/7x-15) | | 384=12c | | p^2-14-38=0 | | 18069333.33333*440*440*1/3 | | 3y=474 | | h-14=3 | | -2+18n-5=-28n+7+3 | | n+-10=30 | | F(x)=x-x+4 | | S^2+4s=27 |